Trichanthera gigantea (Homb. & Bonpl.) Nees, (Acanthaceae) in Cuba - Isidro E. Méndez Santos; Rayner Morales Pérez; Julio C. Rifa Tellez (Agrisost, 2022)
Context: This research is part of the efforts made to establish a new taxonomic approach of family Acanthaceae, and to have an update on the taxa introduced in Cuba. It will also include a verification of its permanence in the land, probable naturalization, and (if it occurs) its later behavior. Aim: To elucidate the current introduction and status of the cultivation or establishment of Trichanthera gigantea (Humb. & Bonpl.) Nees. (Acanthaceae) in Cuba. Methods: Botanical methods were used, such as collection studies, comparison of descriptors, and the keys found in specialized catalogs, along with the description and scientific illustration. The local population was surveyed to check how this species can be useful. Results: This study confirmed the presence of T. gigantea in Cuba, with a detailed analysis of the nomenclature. The taxon was described and illustrated, and the corresponding analytical key was established to contrast it from akin specimens reported in Cuba. Aspects related to its usefulness as a forage-producing plant were tackled as well. Conclusions: T. gigantea should be included in the catalogs and specialized journals on the Cuban flora. The demonstrated usefulness of the plant to produce forage will have to be considered as part of the economic botany, as it will certainly become a factor for the spreading of the plant throughout Cuba.